In vitro Bactericidal Activities of Combination Antibiotic Therapies Against Carbapenem-Resistant Klebsiella pneumoniae With Different Carbapenemases and Sequence Types - Teo, Jocelyn Qi-Min; Fauzi, Nazira; Ho, Jayden Jun-Yuan; Tan, Si Hui; Lee, Shannon Jing-Yi; Lim, Tze Peng; Cai, Yiying; Chang, Hong Yi; Mohamed Yusoff, Nurhayati; Sim, James Heng-Chiak; Tan, Thuan Tong; Ong, Rick Twee-Hee; et al. (Frontiers in Microbiology, 2021)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) is becoming increasingly problematic due to the limited effectiveness of new antimicrobials or other factors such as treatment cost. Thus, combination therapy remains a suitable treatment option. We aimed to evaluate the in vitro bactericidal activity of various antibiotic combinations against CRKP with different carbapenemase genotypes and sequence types (STs). Thirty-seven CRKP with various STs and carbapenemases were exposed to 11 antibiotic combinations (polymyxin B or tigecycline in combination with ß-lactams including aztreonam, cefepime, piperacillin/tazobactam, doripenem, meropenem; and polymyxin B with tigecycline) in static time-kill studies (TKS) using clinically achievable concentrations. Out of the 407 isolate-combination pairs, only 172 (33.1%) were bactericidal (3 log10CFU/mL decrease from initial inoculum). Polymyxin B in combination with doripenem, meropenem or cefepime were the most active, each demonstrating bactericidal activity in 27, 24 and 22 out of 37 isolates, respectively. Tigecycline in combination with ß-lactams were rarely bactericidal. Aside from the lower frequency of bactericidal activity in the dual-carbapenemase producers, there appeared to have no difference in combination activity among the other carbapenemase types. In addition, bactericidal combinations were varied even in strains with similar STs, carbapenemases and other genomic characteristics. Our findings demonstrate that the bactericidal activity of antibiotic combinations is highly strain-specific likely owing to the complex interplay of carbapenem-resistance mechanisms, i.e. carbapenemase genotype alone cannot predict in vitro bactericidal activity. The availability of WGS information can help rationalize the activity of certain combinations. Further studies should explore the utility of genomic markers with phenotypic information to predict combination activity.